The Hourly Apnea-Hypopnea Duration Better Correlates with OSA-Related Nocturnal Hypoxemia and Excessive Daytime Sleepiness Rather Than AHI - Wang Y; Yue W; Zhou B; Zhang J; He Y; Wang M; Hu K (Nature and Science of Sleep)
Yuhan Wang,* Wuriliga Yue,* Beini Zhou,* Jingyi Zhang, Yang He, Mengcan Wang, Ke Hu Department of Respiratory and Critical Care Medicine, Renmin Hospital of Wuhan University, Wuhan, 430060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ke Hu, Department of Respiratory and Critical Care Medicine, Renmin Hospital of Wuhan University, Wuhan, 430060, People’s Republic of China, Email huke-rmhospital@163.comBackground: The apnea-hypopnea index (AHI) has limitations in assessing nocturnal hypoxemia and excessive daytime sleepiness (EDS) in obstructive sleep apnea (OSA) patients. This study evaluated whether hourly apnea-hypopnea duration (HAD) and mean apnea-hypopnea duration (MAD) could complement or outperform AHI.Methods: This study included 1069 OSA patients, of whom 754 completed the Epworth Sleepiness Scale (ESS). Multivariable regression models evaluated the associations between AHI, MAD, HAD, and nocturnal hypoxemia, and standardized Z scores were used for comparison. The predictive ability of AHI, MAD, and HAD models for EDS was evaluated using goodness-of-fit indices, and receiver operating characteristic (ROC) curve analysis was performed using bootstrapping techniques.Results: Nocturnal hypoxemia was observed in 317 participants (29.65%). Patients with nocturnal hypoxemia had significantly higher AHI (43.19 ± 18.41 vs 21.78 ± 14.73 events/hour, P < 0.001) and longer HAD (16.71 ± 7.48 vs 8.24 ± 5.40 minutes, P < 0.001). After adjusting for age, sex, and BMI, AHI and HAD were still significantly associated with nocturnal hypoxemia (P < 0.05). Standardized Z scores analysis revealed that HAD had the strongest association with nocturnal hypoxemia (HAD: OR = 3.69, 95% CI: 3.06− 4.46, P < 0.0001; AHI: OR = 3.48, 95% CI: 2.90− 4.18, P < 0.0001; MAD: OR = 1.01, 95% CI: 0.88− 1.15, P = 0.9314) and mean SpO2 (HAD: β = − 0.91, 95% CI: − 1.02−− 0.79, P < 0.0001; AHI: β = − 0.85, 95% CI: − 0.97−− 0.74, P < 0.0001; MAD: β = 0.00, 95% CI: − 0.12− 0.12, P = 0.9595), outperforming AHI and MAD. The HAD model showed the best fit for predicting EDS, with an area under the curve of 0.61 at a threshold of 5.63.Conclusion: The HAD better correlates with OSA-related nocturnal hypoxemia and EDS rather than AHI. The duration of respiratory events warrants more investigation in clinical assessment.Keywords: obstructive sleep apnea, hourly apnea-hypopnea duration, mean apnea-hypopnea duration, apnea-hypopnea index, nocturnal hypoxemia, excessive daytime sleepiness